2021
DOI: 10.1158/1078-0432.ccr-20-4604
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Afatinib plus Cetuximab for EGFR-Mutant Non–Small Cell Lung Cancer: Results from the Randomized Phase II IFCT-1503 ACE-Lung Study

Abstract: Purpose: Double inhibition of epidermal growth factor receptor (EGFR) using a tyrosine kinase inhibitor plus a monoclonal antibody may be a novel treatment strategy for non–small cell lung cancer (NSCLC). We assessed the efficacy and toxicity of afatinib + cetuximab versus afatinib alone in the first-line treatment of advanced EGFR-mutant NSCLC. Patients and Methods: In this phase II, randomized, open-label study, patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…After confirming the benefit in ORR with osimertinib in the AURA1 trial [58], the phase I/II AURA2 trial [48,59] demonstrated higher ORR and median PFS among patients with T790M secondary mutation combined with common EGFR mutation. The AURA3 study finally concluded with the superiority of osimertinib over platinum-pemetrexed chemotherapy for patients previously treated with EGFR-TKI and harboring a T790M mutation [60].…”
Section: Second-line With Third-generation Egfr-tkismentioning
confidence: 90%
See 1 more Smart Citation
“…After confirming the benefit in ORR with osimertinib in the AURA1 trial [58], the phase I/II AURA2 trial [48,59] demonstrated higher ORR and median PFS among patients with T790M secondary mutation combined with common EGFR mutation. The AURA3 study finally concluded with the superiority of osimertinib over platinum-pemetrexed chemotherapy for patients previously treated with EGFR-TKI and harboring a T790M mutation [60].…”
Section: Second-line With Third-generation Egfr-tkismentioning
confidence: 90%
“…EGFR-TKI Combined with Targeted Therapy Double inhibition of EGFR using EGFR TKI plus EGFR monoclonal antibody (cetuximab) did not show any improvement in terms of PFS for afatinib + cetuximab versus afatinib alone [48].…”
Section: Egfr-tki Treatments Combinationsmentioning
confidence: 93%
“…However, this also clearly shows that adding an anti‐EGFR mAb to afatinib enhances on‐target side effects associated with the inhibition of EGFR. Previous studies with TKI–antibody combinations already showed an increase in TRAEs, which resulted in more than 50% grade ≥3 toxicity 18,29 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with TKI-antibody combinations already showed an increase in TRAEs, which resulted in more than 50% grade ≥3 toxicity. 18,29 In addition, other TKIs such as poziotinib and mobocertinib, specifically designed to target EGFR ex20ins mutations, could not preserve selectivity against wild-type EGFR. During poziotinib treatment, 28% and 26% of patients had grade ≥3 rash and diarrhea TRAEs, respectively.…”
mentioning
confidence: 99%
“…Increased incidence of severe adverse events has been a signi cant concern, and for many of these combination therapies, a clear extension in overall patient survival has not yet been demonstrated. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] In parallel, the emergence of third-generation EGFR-TKIs, particularly those developed in Asia, has been a focal point of recent research. These novel agents are garnering attention for their potential as rst-line treatments for EGFR-mutated NSCLC.…”
Section: Introductionmentioning
confidence: 99%